A negotiation algorithm for decision-making in the construction domain - Idrus A.; Mahmoud M.A.; Ahmad M.S.; Yahya A.; Husen H. (Springer Verlag, 2023)
Artificial intelligence; Autonomous agents; Decision making; Distributed computer systems; Intelligent agents; Multi agent systems; Algorithm architectures; Automated decision making; Automated negotiations; Negotiation algorithm; Pseudo-code; Software agents